Analysis of the Current State and Problems of Teaching Elementary Particle Physics in Pedagogical Institutions of Higher Education - Madaliyev Akmaljon Makhammadjonovich; Qurbanova Dilshunos Kasimjan kizi (Researchparks Publishing, 2023)
This article deals with the situation and problems of teaching particle physics in secondary education, professional education and higher education.